The wider island of Pelops : studies on prehistoric Aegean pottery in honour of Professor Christopher Mee - Smith, David Michael, 1983-; Cavanagh, William G.,; Papadopoulos, Angelos,; Mee, C. (Archaeopress Archaeology, 2023)
This volume explores the myriad ways in which pottery was created, utilized, and experienced in the prehistoric Aegean, across a period of more than 4000 years between the Middle Neolithic and the Early Iron Age transition.